Conditional ablation of macrophages disrupts ovarian vasculature - Turner, Emily C (BioScientifica, 2011)
Macrophages are the most abundant immune cell within the ovary. Their dynamic distribution throughout the ovarian cycle and heterogenic array of functions suggest the involvement in various ovarian processes, but their functional role has yet to be fully established. The aim was to induce conditional macrophage ablation to elucidate the putative role of macrophages in maintaining the integrity of ovarian vasculature. Using the CD11b-diphtheria toxin receptor (DTR) mouse, in which expression of human DTR is under the control of the macrophage-specific promoter sequence CD11b, ovarian macrophages were specifically ablated in adult females by injections of diphtheria toxin (DT). CD11b-DTR mice were given DT treatment or vehicle and ovaries collected at 2, 8, 16, 24 and 48 h. Histochemical stains were employed to characterise morphological changes, immunohistochemistry for F4/80 to identify macrophages and the endothelial cell marker CD31 used to quantify vascular changes. In normal ovaries, macrophages were detected in corpora lutea and in the theca layer of healthy and atretic follicles. As macrophage ablation progressed, increasing amounts of ovarian haemorrhage were observed affecting both luteal and thecal tissue associated with significant endothelial cell depletion, increased erythrocyte accumulation and increased follicular atresia by 16 h. These events were followed by necrosis and profound structural damage. Changes were limited to the ovary, as DT treatment does not disrupt the vasculature of other tissues likely reflecting the unique cyclical nature of the ovarian vasculature and heterogeneity between macrophages within different tissues. These results show that macrophages play a critical role in maintaining ovarian vascular integrity.